2020
DOI: 10.1021/acs.iecr.0c00223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Lightweight Nanocomposite Based on Polyaniline 3D Hollow Spheres Integrated Milled Carbon Fibers for Efficient X-Band Microwave Absorption

Abstract: In the present study, the milled carbon fiber (MCF) and conductive polyaniline (PANI) are impregnated in the epoxy matrix to synthesize a lightweight nanocomposite, providing efficient microwave absorption in the X band. The PANI 3D hollow spheres are uniquely synthesized by removing the polystyrene (PS) core structure of PS/PANI composites. The MCF and as-synthesized PANI hollow spheres are characterized by Raman spectroscopy, X-ray diffraction (XRD), and field emission scanning electron microscopy (FESEM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Interestingly, the RL min value of sample S4 (cf. Figure e) was −7 dB in the measured wavelength range when the filling amount was increased to 40 wt %, which was primarily because too much Ni@GNP filling led to poor impedance matching conditions of the samples (i.e., no effective absorption could be observed in the testing frequency range) . In summary, S3 showed the best performance among all samples and also had excellent RL performance in the C band (from 4 to 8 GHz), which is well known as the frequency band of communication satellite downlink transmission signals.…”
Section: Resultsmentioning
confidence: 91%
“…Interestingly, the RL min value of sample S4 (cf. Figure e) was −7 dB in the measured wavelength range when the filling amount was increased to 40 wt %, which was primarily because too much Ni@GNP filling led to poor impedance matching conditions of the samples (i.e., no effective absorption could be observed in the testing frequency range) . In summary, S3 showed the best performance among all samples and also had excellent RL performance in the C band (from 4 to 8 GHz), which is well known as the frequency band of communication satellite downlink transmission signals.…”
Section: Resultsmentioning
confidence: 91%
“…The electromagnetic characteristics of epoxy nanocomposites with hierarchial carbon nanotube grown on the carbon fiber (CNTCF), Al-substituted copper ferrite (CAF) infused rGO, polyaniline 3D Hollow spheres integrated milled carbon fibers and hetero atom doped carbon derived from chicken feather fibers (CFF) were investigated exclusively in the X band (8.2-12.4 GHz) using the network analyzer by Sandeep Kumar Singh et al and they found that fabricated composites are potential candidates to design a light weight and efficient microwave absorber. [35][36][37][38] However, a review of the literature finds that epoxy composite dielectric investigations are sparse. Epoxy composites are essential because they can be molded into intricate shapes and are suited for devices where flexibility is a key characteristic.…”
Section: Moudam Et Al Applied a Combination Of Dynamic Characterizationmentioning
confidence: 99%
“…The electromagnetic characteristics of epoxy nanocomposites with hierarchial carbon nanotube grown on the carbon fiber (CNTCF), Al‐substituted copper ferrite (CAF) infused rGO, polyaniline 3D Hollow spheres integrated milled carbon fibers and hetero atom doped carbon derived from chicken feather fibers (CFF) were investigated exclusively in the X band (8.2–12.4 GHz) using the network analyzer by Sandeep Kumar Singh et al and they found that fabricated composites are potential candidates to design a light weight and efficient microwave absorber 35–38 …”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic [EM] wave pollution has been growing exponentially in the last couple of years due to the extensive use of EM devices in electronic gadgets and wireless networks for civil, military, and space applications. EM pollution affects the health of humans and disturbs the conventional performance of nearby electronic gadgets in the mode of electromagnetic interference (EMI). The growing flexible electronic requirements for EMI shielding for the next generation are being feather-light, flexible, and thin with a low filler loading, have a uniform dispersion, are easy to process, are environmentally stable, and possess absorption dominant EM shielding. Recently, polymer matrix composites (PMCs) containing electrically conducting carbon nanofillers are considered to be promising EMI shielding materials due to their high conductivity and high dielectric losses along with ease in processing, excellent resistance to corrosion, transparency, , flexibility, thermal stability, tunable performance, and low density as compared to traditional available metal-based EMI shielding materials .…”
Section: Introductionmentioning
confidence: 99%